The Differential Effects of Tai Chi vs. Brisk Walking on Cognitive Function Among Individuals Aged 60 and Greater - Yu, Ye; Zuo, Erfei; Doig, Scott (Frontiers in Human Neuroscience, 2022)
Purpose: The aim of this study was to investigate the differential effects of Tai Chi vs brisk walking on cognitive function among individuals aged 60 and greater. Patients and methods: For participant recruitment, a health talk was arranged at two communities in which two different exercise modalities (Tai Chi and brisk walking) were randomly assigned to participants of each community free of charge. The intervention programs lasted ten weeks, with three 60-min training sessions per week. General cognitive ability and specific cognitive outcomes were measured using the Chinese version of the Montreal Cognitive Assessment (MoCA). Results: A significant interaction on total scores of the MoCA was observed (F = 11.15, p < 0.05). Post-hoc analysis indicated significant improvements on general cognitive performance as measured in performance on the MoCA for both exercise groups at the end of 10 weeks. A significant interaction was only observed on the delayed recall sub-domain (F = 12.93, p < 0.001). Results from post-hoc analysis indicate that the Tai Chi group had a significantly better memory performance relative to brisk walking group (p < 0.05). Specifically, significant improvement was observed in Tai Chi group (p < 0.05), but not in the brisk walking group. Both exercise groups demonstrated significant improvements from baseline to Week 10 , which emerged in visualspatial ability (p < 0.05) and attention performance (p < 0.001). Lastly, animal naming and orientation significantly benefited from brisk walking (p < 0.05) and Tai Chi training (p < 0.05) respectively. Conclusion: Tai Chi and brisk walking as the most commonly used, culture-specific mind-body exercise method have been proven to be effective in improving general cognitive performance and specific cognitive domains. Furthermore, differential effects of two different exercise modalities on cognitive domains were observed, which has provided insightful information for customized exercise programs. Finally, aging individuals who are experiencing cognitive decline should either take Tai Chi classes regularly or engage in brisk walking, which could contribute to brain health.